(a,b,c)-weak contraction in fuzzy metric spaces - Dalal, Sumitra; Masmali, Ibtisam (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
The aim of this paper is to establish some new common fixed point theorems for mappings employing (a,b,c) -weak contraction in fuzzy metric spaces. Our results generalize and improve various well known comparable results.